Pengaruh Profitabilitas dan Struktur Kepemilikan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel InterveninG (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Fauzi, Fendy Ahmad; Ichawnudin, Wawan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2019)
This study aims to examine the effect of profitability and ownership structure on firm value with capital structure as intervening variable. The study was conducted on manufacturing companies listed on the BEI in 2012-2016 with the number of samples taken 13 companies. Data were analyzed using intervening regression and sobel test. Pursuant to result of research known profitability have positive and significant effect to firm value, managerial ownership structure have negative and significant effect to firm value, profitability have negative significant effect to capital structure, ownership structure have negative and significant effect to capital structure and capital structure have positive and significant influence to firm value